Psycho-dynamic Forcefulness through the lens of George R. R. Martin’s A Song of Ice and Fire: A Lacanian Reading - Sulaiman Alhmdni, Thulfiqar Abdulameer; Amjad, Fazel Asadi (International Journal of Psychosocial Rehabilitation, 2025)
A Song of Ice and Fire, which is the focal point of this article, overflows with the subjects as family, obligation and honor strung in confounded courses in our current reality where dream and genuine move side by side. By booming through the first two books of this series, A Game of Thrones and A Clash of Kings, one finds the assortment of the points of view and delves profound into the personalities and their activities which lead to every one of the contentions and disturbances. This effort tries to reveal insight into the convoluted ways and the grave choices of the characters are blossomed that give fierce shake to their entire world; for this we attract upon Lacanian Psychoanalysis to portrait how the most complicated political interests just as the most flawless privileged demonstrations that are seen all through these books are predicated upon desire, which is, as Lacan says, ‘desire of the other’. This work attempts to show the appliance of desire, dynamism and vitality by examining the characters and occasions and afterward talk about the way that the craving of the Other brings forth every code of honor, intolerable hostility, desire for power.